The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1074/jbc.m202594200
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer between the Rieske Iron-Sulfur Protein and Cytochrome c1 in theRhodobacter sphaeroides Cytochromebc1 Complex

Abstract: Electron transfer from the Rieske iron-sulfur protein to cytochrome c 1 (cyt c 1 ) in the Rhodobacter sphaeroides cytochrome bc 1 complex was studied using a ruthenium dimer complex, Ru 2 D. Laser flash photolysis of a solution containing reduced cyt bc 1 , Ru 2 D, and a sacrificial electron acceptor results in oxidation of cyt c 1 within 1 s, followed by electron transfer from the iron-sulfur center (2Fe-2S) to cyt c 1 with a rate constant of 80,000 s ؊1 . Experiments were carried out to evaluate whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 44 publications
3
51
1
Order By: Relevance
“…A rate constant of 1,200 s Ϫ1 was reported when using a binuclear ruthenium complex to rapidly photooxidize cytochrome c 1 in the purified R. sphaeroides bc 1 complex (47). Using the same technique of rapid photoreduce/photooxidize cytochrome c 1 with ruthenium dimer (Ru 2 D), oxidant-induced reduction of cytochrome b H was observed with a rate constant of 250 s Ϫ1 in the presence of antimycin A with bovine bc 1 complex and 1,000 s Ϫ1 with R. sphaeroides bc 1 complex (48). The rate constant of the reduction of heme b H by ubiquinol was found to be 270 s Ϫ1 with a photoreleasable caged ubiquinol substrate with mitochondrial cytochrome bc 1 (36).…”
Section: Presteady-state Reduction Rates Of Cytochrome Bl and Isc By mentioning
confidence: 97%
“…A rate constant of 1,200 s Ϫ1 was reported when using a binuclear ruthenium complex to rapidly photooxidize cytochrome c 1 in the purified R. sphaeroides bc 1 complex (47). Using the same technique of rapid photoreduce/photooxidize cytochrome c 1 with ruthenium dimer (Ru 2 D), oxidant-induced reduction of cytochrome b H was observed with a rate constant of 250 s Ϫ1 in the presence of antimycin A with bovine bc 1 complex and 1,000 s Ϫ1 with R. sphaeroides bc 1 complex (48). The rate constant of the reduction of heme b H by ubiquinol was found to be 270 s Ϫ1 with a photoreleasable caged ubiquinol substrate with mitochondrial cytochrome bc 1 (36).…”
Section: Presteady-state Reduction Rates Of Cytochrome Bl and Isc By mentioning
confidence: 97%
“…However, critical as this parameter is, any kinetic mechanism that recognizes the first electron transfer as the determining step would predict that changes in E m on mutation would be expressed in changes in overall rate constant, so this does not represent a feature unique to the mechanism proposed. The reaction in which ISPH is oxidized has a much higher rate constant, low activation barrier, and is relatively independent of pH (13,14,28), and it would not be rate determining under the experimental conditions used here.…”
Section: Relationship Between Biophysical Properties and Structural Fmentioning
confidence: 99%
“…These two residues thus contribute substantially to the electronegativity responsible for the high potential (E m ϳ300 mV in mitochondria and ␣-proteobacteria (30)) and low pK a values (30 -32). Strains mutated at these and several other residue positions were produced in the bc 1 complex from R. sphaeroides (24,28), Paracoccus denitrificans (25), and in yeast (26). From the variation in rate with driving force, each of these laboratories suggested that the first electron transfer must control the overall rate of QH 2 oxidation.…”
mentioning
confidence: 99%
“…The development of the ruthenium photoreduction method provides an opportunity to measure electron transfer between 2Fe-2S and cyt c 1 in both the forward and reverse directions and thus provides kinetic information on two different initial redox states of cyt bc 1 (10). Moreover, it is becoming clear that the measured rates of electron transfer are probably ratelimited by conformational changes in the ISP (36). The binuclear complex Ru 2 D contains the 2,2Ј:4Ј,4Љ:2Љ,2ٞ-quaterpyridine ligand, which bridges the two ruthenium atoms ( Fig.…”
Section: Determination Of Enzyme Activity and Redox Potential Of The mentioning
confidence: 99%
“…k 1 is attributed to electron transfer from 2Fe-2S to cyt c 1 , whereas k 2 is due to subsequent electron transfer from Q-H 2 to 2Fe-2S and cyt c 1 followed by electron transfer from the semiquinone to cyt b L and cyt b H (Scheme 2) (10). Previous studies of the effects of temperature, pH, and redox potential demonstrated that k 1 is not rate-limited by true electron transfer in the c 1 state but rather is gated by conformational changes from the b state and the mobile state to the active c 1 state (36). According to this analysis, the population of the c 1 state is small but the rate constant for electron transfer from 2Fe-2S to cyt c 1 in the c 1 state is much larger than the observed value of k 1 , 80,000 s…”
mentioning
confidence: 99%